PROLIFERATION AND APOPTOSIS IN RAT MODELS OF ORAL SQUAMOUS CELL CARCINOMA INDUCED BY CAPSAICIN EXTRACT NANOPARTICLE GEL - Widyaningsih, Pratiwi Nur; Aniowati, Fitri; Naim, Cantika Nadrotan; Anggraeni, Nova Dwi (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: Oral Squamous Cell Carcinoma (OSCC) is highly invasive neoplasm of oral epithelial tissue that is moderately differentiated and tends to metastasize rapidly. Capsaicin, a pungent phytochemical in red peppers, exhibits both anti-proliferative and potential pro-cancer effects on human cancer cell lines. Purpose: Determine the proliferation and apoptosis between five groups of rats induced OSCC. Method: 5 groups of treatment; C- (untreated rats), C+ (induced by DMBA), E1 (exposed to DMBA and given cisplatin), E2 (induced by DMBA and Capsaicin extract nanoparticle gel with 1% concentration), and E3 (induced by DMBA and Capsaicin extract nanoparticle gel with a concentration of 3.3%). Maceration method was used to obtain Capsaicin extract from green cayenne pepper, then made into nanoparticle gel. Tissue samples were taken after the treatment was completed, then they were pathologicallyobserved histopathological using IHC to assess apoptic activity via the TUNEL method and proliferative activity using PCNA. Result: The proliferative activity in the E1 group had a significant difference compared to the E2 and E3 groups. E2 and E3 were not significantly different (p-value â‰¥0.05). Apoptotic activity in Group E1 indicated a significant difference from the E2 group and was not significantly different from the E3 group, whereas the E2 and E3 groups were significantly different from each other (p-value â‰¤0.05). Conclusion: The research showed that Capsaicin nanoparticle gel increased apoptotic activity while decreasing proliferative activity in different treatment groups of the OSCC rat model.